2012
DOI: 10.2174/092986710793205345
|View full text |Cite
|
Sign up to set email alerts
|

The Kinetoplastid Chemotherapy Revisited: Current Drugs, Recent Advances and Future Perspectives

Abstract: Leishmaniasis, African sleeping sickness and Chagas disease, caused by the kinetoplastid parasites Leishmania spp, Trypanosoma brucei and Trypanosoma cruzi, respectively, are among the most important parasitic diseases, affecting millions of people and considered to be within the most relevant group of neglected tropical diseases. The main alternative to control such parasitosis is chemotherapy. Nevertheless, the current chemotherapeutic treatments are far from being satisfactory. This review outlines the curr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 0 publications
1
47
0
Order By: Relevance
“…These observations together suggest that new and novel antiparasitic drugs are required. Therefore, the development of alternative drugs for the treatment of the different clinical forms of leishmaniasis is a priority for controlling the disease (Croft et al 2006;Castillo et al 2010). Great efforts have been made to identify potential chemotherapeutic targets in the genome and proteome of Leishmania sp., in the hope of devising more effective treatments (Myler 2008;Concu et al 2009;Chawla and Madhubala 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These observations together suggest that new and novel antiparasitic drugs are required. Therefore, the development of alternative drugs for the treatment of the different clinical forms of leishmaniasis is a priority for controlling the disease (Croft et al 2006;Castillo et al 2010). Great efforts have been made to identify potential chemotherapeutic targets in the genome and proteome of Leishmania sp., in the hope of devising more effective treatments (Myler 2008;Concu et al 2009;Chawla and Madhubala 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Since the 1940s, the pentavalent antimony compounds (e.g., Glucantime, Pentostam, or branded pentavalent formulations) have been the mainstays of antileishmanial therapy (Aït-Oudhia et al, 2011). Although these drugs are usually effective, they produce serious side effects, present difficulties of administration and high cost, the parasite persists in the scars of clinically cured patients (Schubach et al, 1998), and drug resistance has been observed (Castillo et al, 2010). Second-line drugs are used in areas with high rates of unresponsiveness to antimonial treatment or when it was not possible to administrate it.…”
Section: Introductionmentioning
confidence: 99%
“…An estimated 8-10 million people are living with T. cruzi infection in the Latin America (Rassi et al 2010). Compounding this scenario, the available chemotherapy for Chagas' disease is unsatisfactory (Castillo et al 2010). Therefore, novel anti-T. cruzi drugs, ideally directed against new parasite targets, are urgently needed (Sánchez-Sancho et al 2010).…”
Section: Introductionmentioning
confidence: 99%